Optical dimensional metrology at Physikalisch-Technische Bundesanstalt (PTB) on deep sub-wavelength nanostructured surfaces. (18th May 2016) - Bodermann, B; Ehret, G; Endres, J; Wurm, M
Abstract: The dark-field microscopy method with alternating grazing incidence UV illumination (UV-AGID) developed at Physikalisch-Technische Bundesanstalt offers the possibility of measuring individual isolated line structures with linewidths down to the sub-wavelength regime. In contrast, scatterometry is able and already widely used to measure average dimensional parameters of periodic structures down to the deep sub-wavelength regime. Both methods can be used for dimensional measurements of micro- and nanostructures, in particular the critical dimensions (CDs) on wafers or photomasks in the semiconductor industry, complementing each other favourably. Based on numerical simulations, we have investigated the ultimate limits of these two methods in the deep sub-wavelength regime. It has been shown that AGID microscopy in the DUV spectral range is in principle capable of measuring line structures with CDs down to a few 10 nm, depending on the structure material. For scatterometry, no fundamental limit has been observed. In practice, a technical limit due to the limited signal-to-noise ratio is expected for CDs of a few nm in width.